The Microvascular Gap Junction Channel: A Route to Deliver MicroRNAs for Neurological Disease Treatment - Thuringer, Dominique; Solary, Eric; Garrido, Carmen (Frontiers in Molecular Neuroscience, 2017)
Brain microvascular endothelial cells (BMECs) separate the peripheral blood from the brain. These cells, which are surrounded by basal lamina, pericytes and glial cells, are highly interconnected through tight and gap junctions. Their permeability properties restrict the transfer of potentially useful therapeutic agents. In such a hermetic system, the gap junctional exchange of small molecules between cerebral endothelial and non-endothelial cells is crucial for maintaining tissue homeostasis. MicroRNA were shown to cross gap junction channels, thereby modulating gene expression and function of the recipient cell. It was also shown that, when altered, BMEC could be regenerated by endothelial cells derived from pluripotent stem cells. Here, we discuss the transfer of microRNA through gap junctions between BMEC, the regeneration of BMEC from induced pluripotent stem cells that could be engineered to express specific microRNA, and how such an innovative approach could benefit to the treatment of glioblastoma and other neurological diseases.